Management and Microbiological Characteristics of Membrane Formation on a Hydrophilic Acrylic Intraocular Lens: A Clinical Case Series and Material Comparative Study of Different IOLs - Xiaodi Qiu; Yang Wu; Yongxiang Jiang; Yinghong Ji; Xiangjia Zhu; Jin Yang; Yi Lu (Journal of Ophthalmology)
Background/Aims. To report a case series of membrane formation on intraocular lenses (IOLs) after uneventful phacoemulsification and to evaluate the material characteristics and biofilm formation on different IOLs. Methods. Ten eyes implanted with the same type of IOLs were found to have membranes on their IOLs after uneventful phacoemulsification from May 2015 to May 2016. No other patients were found with the same phenomenon among 11236 patients who underwent cataract surgeries during this period. To further investigate the reasons for their formation, we assessed seven types of IOLs used in our hospital, including their material characteristics and the presence of microbes (Staphylococcus epidermidis) on the IOL surface by scanning electron microscopy (SEM). All IOLs were incubated under in vitro flow conditions (BioFlux 1000Z). After 36 h, the IOLs were taken from the system, and both the bound bacteria and biofilm formation were observed. Results. Five eyes underwent intravitreal injections of ceftazidime and norvancomycin with one positive culture obtained from the anterior chamber fluid. The other five eyes only received topical treatment of gatifloxacin/levofloxacin and tobramycin. At the last follow-up, all patients had best-corrected visual acuity (BCVA) of 20/50 or better. In the biofilm study on the IOL surface, Staphylococcus epidermidis biofilms formed more readily on hydrophilic acrylic IOLs than on hydrophobic acrylic IOLs. Conclusions. Bacterial adhesion and biofilm tend to develop on certain types of IOLs because of the characteristics of the biomaterial.